2016
DOI: 10.1002/1873-3468.12065
|View full text |Cite
|
Sign up to set email alerts
|

Membrane interactions and self‐association of components of the Ess/Type VII secretion system of Staphylococcus aureus

Abstract: The Ess/Type VII protein secretion system, essential for virulence of pathogenic Staphylococcus aureus, is dependent upon the four core membrane proteins EssA, EssB, EssC and EsaA. Here, we use crosslinking and blue native PAGE analysis to show that the EssB, EssC and EsaA proteins individually form homomeric complexes. Surprisingly, these components appear unable to interact with each other, or with the EssA protein. We further show that two high molecular weight multimers of EssC detected in whole cells are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
1
30
2
Order By: Relevance
“…system (73,74). The EccC-related protein EssC SA (75,76) includes a twin-FHA domain that is essential for secretion (77). FHA domains also mediate oligomerization (78)(79)(80).…”
Section: Figmentioning
confidence: 99%
“…system (73,74). The EccC-related protein EssC SA (75,76) includes a twin-FHA domain that is essential for secretion (77). FHA domains also mediate oligomerization (78)(79)(80).…”
Section: Figmentioning
confidence: 99%
“…In vivo crosslinking analysis indicated that Ess membrane proteins homo-12 multimerise [52] Although multimerisation of Thermomonospora curvata EccC 13 is controlled by substrate interactions, EssC multimerisation was observed in 14 a strain of S. aureus lacking core Ess components and substrates. [52].…”
mentioning
confidence: 99%
“…[52]. Thus, 15 even if these ATPases show significant sequence homology, there appear to 16 be differences in the control of their assembly and activity.…”
mentioning
confidence: 99%
“…To determine whether it is an integral membrane protein we washed isolated membranes with urea which removes peripherally bound proteins by denaturation. Fig 2B indicates that a large fraction of TspA-Myc is displaced from the membrane to the cytoplasmic fraction by urea whereas a bona fide integral membrane protein, EssB, is not displaced by this treatment 24, 25, 26 . We conclude that TspA-Myc peripherally interacts with the membrane.…”
Section: Resultsmentioning
confidence: 95%